Effect of bilateral oophorectomy on women's long-term health. (September 2009) - Parker, William H; Jacoby, Vanessa; Shoupe, Donna; Rocca, Walter
Bilateral oophorectomy at the time of hysterectomy for benign disease is commonly practiced in order to prevent the subsequent development of ovarian cancer or other ovarian pathology that might require additional surgery. At present, bilateral oophorectomy is performed in 78% of women aged between 45 and 64 years having a hysterectomy, and a total of approximately 300, 000 prophylactic oophorectomies are performed in the USA every year. Estrogen deficiency resulting from pre- and post-menopausal oophorectomies has been associated with higher risks of coronary heart disease, stroke, hip fracture, Parkinsonism, dementia, cognitive impairment, depression and anxiety in many studies. While ovarian cancer accounts for 14, 800 deaths per year in the USA, coronary heart disease accounts for 350, 000 deaths per year. In addition, 100, 000 cases of dementia may be attributable annually to prior bilateral oophorectomy. At present, observational studies suggest that bilateral oophorectomy may do more harm than good. In women who are not at high risk of developing ovarian or breast cancer, removing the ovaries at the time of hysterectomy should be approached with caution.